EFFECT OF SOME SYSTEMIC HERBICIDES ON GROWTH OF PURPLE NUTSEDGE ( Cyperus rotundus L.) - A . M . Sultan (Mesopotamia Journal of Agriculture, 2006)
The factorial pot experiment was conducted in order to investigate the effect of some systemic herbicides ( Topik 60 , Focus ultra 300 , Fusaltat 66 and Glyphosate 930 cm3 a.i /ha) and unweeded check treatment when it applied Tween 20(for wax removing from leaves)on growth and production of tubers of purple nutsedge ( Cyperus rotundus L. ) in summer season 2005 at Agric and Forestry college , Mosul univ. Data were collected after 107 day of sowing tubers . The significant result indicate that Glyphosate had more efficiency for reduce plant growth by reducing dry weight of roots , number , weight and size of tubers up to 49.2 , 52.5 and 63.6 % ,respectively comparison with check treatment , while Focus ultra herbicide had increased number ,weight and size of nutsedge tubers up to 50 ,24 and 29 % ,respectively. Others herbicides had less effectiveness . However the wax on the nutsedge leaves did not effect on herbicides absorption and toxicity of the plants . Therefore insignificant result had seen when it used material for wax removal (T20) . There was positive correlation between shoot growth ( number of leaves and branches ) number , weight and size of new formation tubers , while number of tuber have negative correlation with weight of new tubers .